Solute Reservoirs Reflect Variability of Early Diagenetic Processes in Temperate Brackish Surface Sediments - Lipka, Marko; Woelfel, Jana; Gogina, Mayya; Kallmeyer, Jens; Liu, Bo; Morys, Claudia; Forster, Stefan; Böttcher, Michael E. (Frontiers in Marine Science, 2018)
Coastal marine sediments are a hotspot of organic matter degradation. Mineralization products of early diagenetic processes accumulate in the pore waters of the sediment, are subject of biological uptake and secondary biogeochemical processes and are released back into the water column via advective and diffusive fluxes across the sediment-water interface. Seven representative sites in the shallow coastal area of the southern Baltic Sea (15–45 m water depth), ranging from permeable sands to fine grained muds, were investigated on a seasonal basis for their key mineralization processes as well as their solid phase and pore water composition to identify the drivers for the variability of early diagenetic processes in the different sediment types. The sandy sediments showed about one order of magnitude lower organic carbon contents compared to the muds, while oxygen uptake rates were similar in both sediment types. Significantly higher oxygen uptake rates were determined in two near-shore muddy sites than in a deeper coastal muddy basin, which is due to higher nutrient loads and the corresponding addition of fresh algal organic matter in the near-shore sites. Pore water concentration profiles in the studied sediments were usually characterized by a typical biogeochemical zonation with oxic, suboxic, and sulfidic zones. An up to 15 cm thick suboxic zone was sustained by downward transport of oxidized material in which dissolved iron and phosphate indicate an intensive reduction of reactive Fe with the release of adsorbed phosphorus. While the geochemical zonation was stable over time in the muds of the studied deeper basin, high variability was observed in the muds of a near-coastal bay probably mainly controlled by sediment mixing activities. The sediments can be characterized by essentially two factors based on their near-surface benthic solute reservoirs: (1) their organic matter mineralization and solute accumulation efficiency and (2) their redox-state. Benthic solute reservoirs in the pore waters of the top decimeter were generally higher in the muddy than in the sandy sediments as the more permeable sands were prone to an intensive exchange between pore water and bottom water. The three studied muddy sites showed great dissimilarities with respect to their predominating redox-sensitive metabolites (dissolved iron, manganese, and sulfide). Surface-near advective transport like irrigation of permeable sands and rearrangement of cohesive muds had a particularly strong influence on early diagenetic processes in the studied sediments and were probably the most important cause for the spatiotemporal variability of their benthic solute reservoirs.